Transcriptomic and co-expression network analyses on diverse wheat landraces identifies candidate master regulators of the response to early drought - Barratt, Liam J.; Reynolds, Isaac J.; Franco Ortega, Sara; Harper, Andrea L. (Frontiers in Plant Science, 2023)
Over four billion people around the world rely on bread wheat (Triticum aestivum L.) as a major constituent of their diet. The changing climate, however, threatens the food security of these people, with periods of intense drought stress already causing widespread wheat yield losses. Much of the research into the wheat drought response has centred on the response to drought events later in development, during anthesis or grain filling. But as the timing of periods of drought stress become increasingly unpredictable, a more complete understanding of the response to drought during early development is also needed. Here, we utilized the YoGI landrace panel to identify 10,199 genes which were differentially expressed under drought stress, before weighted gene co-expression network analysis (WGCNA) was used to construct a co-expression network and identify hub genes in modules particularly associated with the early drought response. Of these hub genes, two stood out as novel master regulators of the early drought response – one as an activator (TaDHN4-D1; TraesCS5D02G379200) and the other as a repressor (uncharacterised gene; TraesCS3D02G361500). We propose that these hub genes may be able to regulate the early drought response due to their likely control over the expression of members of gene families well-known for their involvement in the drought response in many plant species, namely dehydrins and aquaporins, as well as other genes seemingly involved in key processes such as, stomatal opening, stomatal closing, stomatal morphogenesis and stress hormone signalling.